PENGARUH TERAPI MUSIK SHOLAWAT PADA LANSIA DENGAN GANGGUAN POLA TIDUR DI WILAYAH KERJA PUSKESMAS TANJUNG (DESA PLAMPAAN), SAMPANG - Prastomo; Taufiqur Rahman; Ali Mahsun (Jurnal Cakrawala Ilmiah, 2024)
Elderly usually experience physical changes and decreased sleep quality. Sleep quality is a person's ability to maintain his sleep state to get sleep according to sleep needs. Disturbances in sleep patterns that often occur in the elderly are basically difficult to maintain sleep and if you wake up at night it is difficult to get back to sleep. To overcome this disorder, namely by providing sholawat music therapy so that it can have a therapeutic effect on the elderly. Method: pre-Experimental (One Group Pre-Post Test Design) with using the purposive Sampling method with a total sample of 20 people. Collecting data using a questionnaire with a Likert scale. The data obtained were processed by editing, coding, scoring, tabulating, interpreting and statistically analyzed using normality, homogeneity, Wilcoxon tests. Results: the majority of respondents obtained based on changes in sleep quality before being given music therapy in the Work Environment of the Tanjung Health Center (Plampaan Village) as many as 13 respondents (56%) experienced poor sleep quality, and most of the respondents based on changes in good sleep quality as many as 12 people (60 %). Wilcoxon test (p value = 0.000 ≤ α = 0.05). Conclusion: from the results of the Wilcoxon test, there is an effect of music therapy on the sleep quality of the elderly in the Work Environment of the Tanjung Public Health Center (Plampaan Village).